Community-based Intravenous Treatment and Central Venous Access Devices: A Scoping Review of the Consumer and Caregiver Experience, Information Preferences, and Supportive Care Needs. Issue 1 (2nd January 2023) - Sharp, Rebecca; Xu, Qunyan; Corsini, Nadia; Turner, Lisa; Altschwager, Jodie; Marker, Julie; Ullman, Amanda; Esterman, Adrian
ABSTRACT: Purpose: Map existing research and describe the consumer/caregiver experience of community-based intravenous treatment, central venous access devices (CVADs), supportive care needs, and information preferences. Design: Scoping review. Methods: Five databases (Joanna Briggs Institute, Cochrane library, Emcare, Embase, and Medline) were searched. Screening and data extraction were performed independently by two reviewers. Findings: Forty-eight studies were included Conclusions: Although community-based intravenous treatment and CVADs have a significant impact on consumers and caregivers, there is scant research on their supportive care needs and information preferences. Clinical Evidence: Some consumers and caregivers may require additional support while undergoing community-based intravenous treatment.